(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Endometrial polyps are a frequent cause of abnormal uterine bleeding (AUB) in women of reproductive and perimenopausal age. Accurate, noninvasive diagnosis is essential for appropriate management. Transvaginal ultrasound (TVS) is widely used for evaluating endometrial pathology, but its diagnostic accuracy varies across studies. Objective: To determine the diagnostic accuracy of transvaginal ultrasound in detecting endometrial polyps, using histopathology as the gold standard. Methods: This cross-sectional study was conducted in the Department of Diagnostic Radiology, Lahore General Hospital / PGMI, Lahore, and included 112 women aged 22–45 years presenting with AUB. All underwent TVS followed by histopathological evaluation of endometrial tissue obtained by biopsy or hysteroscopy. Diagnostic indices, including sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall accuracy, were calculated using histopathology as the reference standard. Results: Endometrial polyps were confirmed on histopathology in 16 (14.3%) patients. TVS identified polyps in 58 (51.8%) cases. The diagnostic performance of TVS was: sensitivity 68.8%, specificity 51.0%, PPV 19.0%, NPV 90.7%, and overall accuracy 53.6%. The high NPV indicated good reliability of TVS in ruling out endometrial polyps, whereas the low PPV reflected over-diagnosis due to overlapping sonographic features with other endometrial conditions. Conclusion: Transvaginal ultrasound is a useful, noninvasive, and readily available screening tool for detecting endometrial polyps in women with AUB. A negative TVS reliably excludes polyps; however, positive findings should be confirmed by hysteroscopy and histopathology before therapeutic intervention.